Customization of KOHA Integrated Library System (ILS) Interface for Better Usability - Neupane, Rajendra (Access: An International Journal of Nepal Library Association, 2023)
This study describes the usability of KOHA Integrated Library System (ILS).KOHA is an integrated library system widely used in Nepal. The main objective of this paper is to compare the usability of KOHA ILS before and after the customization of the interface. For this, five military libraries in Nepal have been purposively surveyed which are currently using customized version of KOHA ILS. The questionnaire was developed to address the eight usability matrices. The study found that all of the military libraries surveyed have been using KOHA ILS. Before customization and update to the latest version of KOHA the librarians and the users were unable to utilize the full features of the software. It is also found that the customization of interfaces has improved the usability of KOHA ILS. Hence it is concluded that the customization of interface is required for the better usability.